Identification and Characterization of Phenylpropanoid Biosynthetic Genes and Their Accumulation in Bitter Melon (Momordica charantia) - Cuong, Do Manh (Molecules, 2018)
Phenylpropanoids and flavonoids belong to a large group of secondary metabolites, and are considered to have antioxidant activity, which protects the cells against biotic and abiotic stresses. However, the accumulation of phenylpropanoids and flavonoids in bitter melon has rarely been studied. Here, we identify ten putative phenylpropanoid and flavonoid biosynthetic genes in bitter melon. Most genes were highly expressed in leaves and/or flowers. HPLC analysis showed that rutin and epicatechin were the most abundant compounds in bitter melon. Rutin content was the highest in leaves, whereas epicatechin was highly accumulated in flowers and fruits. The accumulation patterns of trans-cinnamic acid, p-coumaric acid, ferulic acid, kaempferol, and rutin coincide with the expression patterns of McPAL, McC4H, McCOMT, McFLS, and Mc3GT, respectively, suggesting that these genes play important roles in phenylpropanoid and flavonoid biosynthesis in bitter melon. In addition, we also investigated the optimum light conditions for enhancing phenylpropanoid and flavonoid biosynthesis and found that blue light was the most effective wavelength for enhanced accumulation of phenylpropanoids and flavonoids in bitter melon.